At Least Agree on the Important Things: The Impact of Issue Distance, Intracoalition Heterogeneity, and Salience on Voters' Coalition Preferences - Robert Welz (Politische Vierteljahresschrift, 2022)
The 2021 German federal election led to the formation of the so-called traffic-light coalition between the Social Democratic Party, the Green Party, and the Free Democratic Party, which had never before been agreed upon at the federal level. Over a~long period, German parties had competed for government in relatively clear and ideologically homogeneous camps. However, fragmentation of the party system made majorities for two-party alliances more and more unlikely, and party elites needed to reassess new partnerships. Most of these novel coalitions, like the traffic-light coalition, are also cross-cutting dimensions of political competition in Germany. This raises the question of how voters reflect upon these novel government alternatives and make up their minds about which of them they would like to see in office. In this paper, I~argue that a~nuanced view on issues rather than general ideology offers more precise insights on the origins of voters' coalition preferences. Furthermore, as salience theory suggests, not every issue is equally important for every part of the citizenry. Therefore, it is expected that the effects of voter–coalition distance as well as intracoalition heterogeneity on specific issues are moderated by individuals' saliency of the respective issues. These expectations are tested using data from the 2021 preelection cross-section survey of the German Longitudinal Election Study. The results emphasize the relevance of specific issues as well as salience in the formation of voters' coalition preferences. – – Mit der Ampelkoalition aus SPD, Die Grünen und FDP formierte sich nach der Bundestagswahl 2021 ein für die Bundesebene neues Regierungsbündnis. Über einen langen Zeitraum hinweg konkurrierten die deutschen Parteien in vergleichsweise klaren und ideologisch homogenen Lagern um die Regierungsverantwortung. Die Fragmentierung des Parteiensystems machte Mehrheiten für Zweiparteienbündnisse jedoch immer unwahrscheinlicher, und die Parteien waren gezwungen, neue Allianzen zu erwägen. Diese neuen Koalitionsmodelle lassen sich nicht mehr eindeutig entlang der klassischen Dimension politischen Wettbewerbs in Deutschland verorten. Dies wirft die Frage auf, wie die Wähler*innen diese neuen Regierungsalternativen bewerten. Dieser Beitrag argumentiert, dass eine differenzierte Betrachtung von Politikfeldern anstelle allgemeinerer Ideologie genauere Erkenntnisse über die Ursprünge der Koalitionspräferenzen der Wähler bietet. Außerdem legt die Salienztheorie nahe, dass nicht jedes Politikfeld für jede*n Bürger*in gleichermaßen von Bedeutung ist und daher die Effekte der politikfeldspezifischen Distanz zwischen Wähler*in und Koalition sowie der innerkoalitionären Heterogenität von der Salienz eines Politikfelds moderiert werden. Diese Erwartungen werden mit Daten der Vorwahl-Querschnittsbefragung 2021 der German Longitudinal Election Study (GLES) getestet. Die Ergebnisse unterstreichen die Relevanz spezifischer Themenfelder sowie der Salienz für die Koalitionspräferenzen der Wähler*innen.
Keywords: 320; Coalition governments; Voters' preference formation; Coalition policy positions; Spatial model; German Federal Election 2021; Koalitionsregierungen; Präferenzbildung der Wähler*innen; Koalitionspositionen; Räumliches Modell; Bundestagswahl 2021